APLIKASI SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN EDITOR BAHASA DI REDAKSI FORUM EDUKASI DENGAN METODE TOPSIS - Siti Nur Utami; Asih Winantu (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2018)
Searching for the right editor in the Editor Education Forum needs the right analysis so the editor's selection really fits the criteria that later can publish good quality books. Therefore, determining the editor for book editors requires a structured and systematic procedure that can be accounted for, namely through selection. This research was conducted to find a solution that can help the manager in selecting a prospective language editor. The method used to select prospective editors is using the TOPSIS method. This method is one method of decision making that is widely used to select practical decision making. TOPSIS has a concept where the chosen alternative is the best alternative that has the shortest distance from the positive ideal solution and the farthest distance from the negative ideal solution. With the Application of Support Systems this decision can help and facilitate the manager to select prospective editors who are in accordance with their respective fields. The final result of the calculation on the decision support system application is displaying ranking as a reference in giving a decision.